Sustainable Financial Management Strategies in Islamic Banks Amid Global Economic Volatility - Ahadi Rerung; Ana Rusmardiana; Firda Rachma Amalia; Abdul Karim (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study explores the sustainable financial management strategies implemented by Islamic banks amid global economic volatility. this study aims to identify and analyze the sustainable financial management strategies implemented by Islamic banks in the face of global economic volatility. Using a qualitative approach through a literature review, the research examines existing studies and theoretical frameworks related to risk management, investment strategies, and financial sustainability in Islamic banking. The findings reveal that Islamic banks prioritize Shariah-based risk management, focusing on asset-backed instruments such as sukuk and mudharabah, which are more stable and resilient during financial crises. Additionally, diversification strategies in sectors like renewable energy, infrastructure, and social impact investments are increasingly adopted to mitigate risk and ensure long-term stability. The study also highlights the role of sustainable investment policies that align financial profitability with social responsibility, reflecting the ethical foundations of Islamic finance. The study concludes by emphasizing the need for further empirical research to better understand the implementation of these strategies across global contexts. The findings provide insights for policymakers, financial institutions, and researchers seeking to strengthen the resilience and sustainability of Islamic banks in a volatile economy.